FORMATION OF CREATIVE PERSONALITY OF A FUTURE TEACHER BY MEANS OF COMMUNICATIVE-CREATIVE APPROACH TO TEACHING HUMANITIES IN CHILDREN'S CHILDREN (Pedagogy of Higher and Secondary Education, 2010)
In this article the formation of creative personality of future teacher by means of communicatively-creative approach in the process of teaching of human disciplines is considered.
Keywords: creativity; communicatively-creative approach; linguistic creativity; creative features of personality; integrative ability for creation